The fringes of citizenship Romani minorities in Europe and civic marginalisation - Sardelic, Julija (Theory for a Gobal Age, 2021)
This book presents a socio-legal enquiry into the civic marginalisation of Roma in Europe. Instead of looking only at Roma's position as migrants, an ethnic minority or a socio-economically disadvantage group, it considers them as European citizens, questioning why they are typically used to describe exceptionalities of citizenship in developed liberal democracies rather than as evidence for how problematic the conceptualisation of citizenship is at its core. Developing novel theoretical concepts, such as the fringes of citizenship and the invisible edges of citizenship, the book investigates a variety of topics around citizenship, including migration and free movement, statelessness and school segregation, as well as how marginalised minorities respond to such predicaments. It argues that while Roma are unique as a minority, the treatment that marginalises them is not. This is demonstrated by comparing their position to that of other marginalised minorities around the globe.